Geothermal heat flux in Greenland and its influence upon the ice sheet model topography - O. O. Rybak (Lëd i Sneg, 2015)
The paper describes procedures of verification and subsequent correction by means of mathematical modeling of a field of geothermal heat flux aimed at the following application of the field in numerical experiments with the Earth system model. The main component of the system is the Greenland ice sheet which is investigated here. The corrected field of the geothermal heat flux is tested for a case when the field is reconstructed from data of measured atmospheric precipitation sums as well as for a field generated by means of simple model of the water-heat balance. This simple model is used as a buffer between the general atmosphere circulation model and the ice sheet model.